Analisis Manajemen Strategi Pd. Kecap Zebra Dalam Menghadapi Persaingan Yang Semakin Kompetitif - Rosa, Edy Safni (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2010)
This research was conducted to see the internal and external faktors on Zebra Soy Saouce Company in facing a more competitive rivalry and providing some alternatives that can be used by the company in facing the business enviromental change. Basic analysis of matrix IE,and industrial rivalry analysis )five Factors of Porters) were used to direct the company positioning. Industrial rivalry analysis of the Soy Sauce industry in Indonesia indicates that the degree of competitiveness within the industry is medium. The degree of threat from the new entrant and product substitute are medium.Barganing power of the supplier and purchaser is also medium. From the analysis, itâs shown that the strengths of Zebra Soy Souce Company are the acces to the supplier of a good quality product, strong market network, its product varietes, good company image and competitive product price. The weaknesses of the company are human resources, location of the company, type and the degree of sophistication of technology, and its capacity. The present opportunities of the company are the change of customes way of the life and consumption level of the soy sauce,exchange rate of rupiah,export policy, investment policy, the depelovment of processing technology, transportation and use of internet and e-commerce. On the other hand, the threats among other are a slow down of the economic growth, fluctuation of soybean price, political and secury situation, environmental policy, infalation and interest rate. Keywords; Manajemen Strategi,